Temporal order is coded temporally in the brain: early event-related potential latency shifts underlying prior entry in a cross-modal temporal order judgment task - Vibell, J; Klinge, C; Zampini, M; Spence, C; Nobre, A (Cognitive Neuroscience Institute, 2007)
The speeding-up of neural processing associated with attended events (i.e., the prior-entry effect) has long been proposed as a viable mechanism by which attention can prioritize our perception and action. In the brain, this has been thought to be regulated through a sensory gating mechanism, increasing the amplitudes of early evoked potentials while leaving their latencies unaffected. However, the majority of previous research has emphasized speeded responding and has failed to emphasize fine temporal discrimination, thereby potentially lacking the sensitivity to reveal putative modulations in the timing of neural processing. In the present study, we used a cross-modal temporal order judgment task while shifting attention between the visual and tactile modalities to investigate the mechanisms underlying selective attention electrophysiologically. Our results indicate that attention can indeed speed up neural processes during visual perception, thereby providing the first electrophysiological support for the existence of prior entry.